Community-based Mental Healthcare: A Case Study in a Cross-border Region of Germany and the Netherlands - Lohmeyer, Franziska Michaela; Commers, Matthew J.; Leoncini, Emanuele; Specchia, Maria Lucia; Boccia, Stefania; Ricciardi, Walter Gualtiero; de Belvis, Antonio Giulio (Das Gesundheitswesen, 2019)
Background Community-based mental healthcare (CBMH) aims at supplying psychiatric patients with rehabilitative care outside the hospital. The aim of this study was to compare the organization of CBMH in a cross-border region of Germany and the Netherlands.Method Semi-structured interviews gave insight into characteristics of CBMH approaches applied in the German region of Aachen (IHP) and the Dutch Province of Limburg (FACT). We applied a Delphi technique to select a performance indicator (PI) set for CBMH, which served as a conceptual model to allow comparison.Results Both approaches are flexible, patient-centred and include the evaluation of quality. Both provide financial and administrative support for the access.Conclusion CBMH approaches appear to be equally valid from several perspectives even if they revealed, at the same time, important differences related to scope, integration with non-CBMH care resources and geographic coverage. Secondarily, the study provides a contribution to the development of a PI set to compare and evaluate CBMH approaches.
Keywords: community-based care; performance indicators; mental health; case management